Pengaruh Mata Kuliah Kewirausahaan dan Motivasi Berwirausaha terhadap Pembentukan Jiwa Green Entrepreneur Mahasiswa - Devita Meliani; Lifa Farida Panduwinata (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2022)
The purpose of this study was to determine the effect of entrepreneurship education and entrepreneurial motivation on the formation of the entrepreneurial spirit of green students. This is because movements in Indonesia are still a problem that needs attention. The government's effort to overcome this problem is by requiring every university in Indonesia to add a compulsory subject, namely entrepreneurship, one of which has been implemented in the Office Administration Education Study Program, State University of Surabaya. The research method used is descriptive quantitative, then sampling using probability sampling with a simple random sampling technique. The data collection instrument used a questionnaire with closed questions. As for the data analysis in this study using multiple linear regression. After the observations were made, it turned out that only a few students had implemented the learning both theory and practice that they had acquired during the entrepreneurship course.